Effectiveness of Five-Finger Relaxation Combination Therapy With Nature Sound Music on Patient Dm Type 2 - Elenia Cristiani Putri, Monica; Dewi Astuti, Agnes; Christyanni, Yuyun; Datak, Gad; Sulistyowati, Reny; Inung Sylvia, Ester (LPPM Universitas Duta Bangsa Surakarta, 2024)
Patients with diabetes mellitus have long-term health problems that impact both their physical and mental well-being. One of the psychological effects that people with diabetes mellitus frequently encounter is depression. Patients with diabetes mellitus can benefit from non-pharmacological therapies such as music therapy and five-finger relaxation therapy to lessen stress and despair. This research aims to ascertain the impact on depression in patients with type 2 diabetes in the city of Palangka Raya of combining five-finger relaxation therapy with natural sound music. A quasi-experimental pretest-posttest design with a control group used in this research. Using a purposive sample approach, this research was carried out at the Kayon Health Center UPT and the Pahandut Health Center BLUD UPT, with 30 respondents in each group. The intervention group was given five-finger relaxation therapy with nature sound music and the control group only received five-finger relaxation therapy. Respondents' degree of depression was assessed both before and after the intervention using the Beck Depression Inventory II (BDI II) scale. Research results proved that type 2 DM patients in the city of Palangka Raya saw a significant reduction in depression when five-finger relaxation therapy and nature sound music were implemented together (P = 0.041).